Peran Perpustakaan Digital Dalam Pembelajaran Literasi Digital Siswa Sekolah Dasar - Muhammad Ridlwan; Almaytasa Munfarikah; Lana Camelya; Muhammad Nofan Zulfahmi (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
The rapid development of information and communication technology has changed the way students access information and learn, making digital libraries an important resource for digital literacy learning in primary schools. This research aims to explore the role of digital libraries in enhancing digital literacy learning of primary school students. The methods used included a literature study and a survey of students and teachers in several primary schools. The results showed that digital libraries not only provide easy access to various information sources, but also provide tools and platforms that support the development of students' critical, analytical and creative skills. In addition, the digital library serves as a collaborative space that encourages interaction between students and teachers and between students and other learning resources. The implications of this study highlight the importance of integrating digital libraries into the school curriculum to maximise the learning potential of digital literacy among primary school students. Thus, the utilisation of digital libraries is expected to improve the quality of education and digital literacy skills of students in today's information age.